Pemeriksaan Kesehatan dan Sosialisasi Penggunaan Kinesiotaping - Rezki Amalia Nurshal (PPNI UNIMMAN, 2024)
The main aim of this activity is to increase public awareness regarding the importance of health and introduce kinesiotaping as an alternative therapy method to treat various musculoskeletal problems. Health checks include checking blood pressure, blood sugar levels, cholesterol, as well as general health consultations, giving the public the opportunity to get medical advice directly from health workers. In addition, socialization of the use of kinesiotaping is carried out through demonstrations of installation techniques and practical applications to reduce muscle pain and improve joint function. The results of the activity showed a positive response from the public who felt more aware of the importance of maintaining health and understanding the benefits of kinesiotaping. This activity also succeeded in strengthening relations between the university and the local community, with the hope of continuing to improve health education in the future.